2022
DOI: 10.1155/2022/5194523
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ginsenoside Rh2 on Cardiomyocyte Pyroptosis in Rats with Acute Myocardial Infarction

Abstract: Objective. This paper intends to verify through in vivo experiments whether ginsenoside Rh2 (G-Rh2) can play an anti-inflammatory role by modulating cardiomyocyte (CM) pyroptosis in rats with acute myocardial infarction (AMI), thereby alleviating myocardial injury. Methods. Twenty SD rats were randomized into control, L-Rh2, M-Rh2, and H-Rh2 groups, among which the latter three groups were modeled for AMI and given an intraperitoneal injection of G-Rh2 (L-Rh2: 2 mg/kg; M-Rh2: 4 mg/kg; H-Rh2: 8 mg/kg), while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“… 68 At present, a number of traditional Chinese herbal medicine preparations broadly applied in clinical practice to treat MI, such as Qishen Granules and Ginsenoside Rh2(G-Rh2), have also been confirmed to inhibit the development of AMI by alleviating CM pyroptosis. 69 , 70 G-Rh2, a hydrolysate derived from ginsenoside which is the active constituent of ginseng, was recently found to significantly ameliorate the severe damage to CMs and organelles in AMI-modeled rat CMs, with marked inhibition of both NLRP3 and caspase-1 levels. 70 …”
Section: Mechanisms For the Involvement Of Pyroptosis In Coronary Hea...mentioning
confidence: 99%
See 1 more Smart Citation
“… 68 At present, a number of traditional Chinese herbal medicine preparations broadly applied in clinical practice to treat MI, such as Qishen Granules and Ginsenoside Rh2(G-Rh2), have also been confirmed to inhibit the development of AMI by alleviating CM pyroptosis. 69 , 70 G-Rh2, a hydrolysate derived from ginsenoside which is the active constituent of ginseng, was recently found to significantly ameliorate the severe damage to CMs and organelles in AMI-modeled rat CMs, with marked inhibition of both NLRP3 and caspase-1 levels. 70 …”
Section: Mechanisms For the Involvement Of Pyroptosis In Coronary Hea...mentioning
confidence: 99%
“… 69 , 70 G-Rh2, a hydrolysate derived from ginsenoside which is the active constituent of ginseng, was recently found to significantly ameliorate the severe damage to CMs and organelles in AMI-modeled rat CMs, with marked inhibition of both NLRP3 and caspase-1 levels. 70 …”
Section: Mechanisms For the Involvement Of Pyroptosis In Coronary Hea...mentioning
confidence: 99%
“…Ginsenosides were considered the main bioactive components contributing to these actions. Several minor ginsenosides were reported to exert inhibitory effects on NLRP3 inflammasome in a variety of animal models, including depression [ 30 ], myocardial infarction [ 31 ], and d -galactosamine/LPS-induced liver injury [ 32 ]. Our pilot study indicated that ginsenoside Rk2 (Rk2) showed the most potent anti-inflammatory activity induced by activation of NLRP3 inflammasome without overt cytotoxicity, among the tested minor ginsenosides ( Fig.…”
Section: Introductionmentioning
confidence: 99%